1994
DOI: 10.1021/jm00028a016
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the design of .sigma.-2-selective ligands: synthesis and evaluation of N-[2-(3,4-dichlorophenyl)ethyl]-N-methyl-2-(1-pyrrolidinyl)ethylamine-related polyamines at .sigma.-1 and .sigma.-2 receptor subtypes

Abstract: A series of polyamines based on the high affinity sigma receptor ligand N-[2-(3,4-dichlorophenyl)-ethyl]-N-methyl-2-(1-pyrrolidinyl)ethylamine (3) were developed and evaluated for their binding characteristics at sigma-1 and sigma-2 receptor subtypes. The data indicated that a considerable degree of structural variation is possible while still retaining nanomolar affinity at sigma receptors. As the structure of the polyamines was varied, their binding at sigma-1 and sigma-2 subtypes showed quite different and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…The r 1 selectivity observed for SA4503 is 10 to 1 based upon IC 50 ratios, and 14 to 1 using K i values despite the higher r 1 affinity of SA4503 in our hands (6.67 nM vs. 17.4 nM IC 50 ). We and others (Cobos et al, 2005;de Costa et al, 1994;DeHaven-Hudkins et al, 1992), also note 3-to 5-fold higher r 1 affinities than Matsuno et al (1996), reported for the reference compounds (þ)-pentazocine (IC 50 ¼ 13.7 nM) and DTG (IC 50 ¼ 246 nM) in the original SA4503 work. This suggests a systematic, but not easily distinguished, difference between the r 1 receptor assays.…”
Section: Discussionsupporting
confidence: 50%
“…The r 1 selectivity observed for SA4503 is 10 to 1 based upon IC 50 ratios, and 14 to 1 using K i values despite the higher r 1 affinity of SA4503 in our hands (6.67 nM vs. 17.4 nM IC 50 ). We and others (Cobos et al, 2005;de Costa et al, 1994;DeHaven-Hudkins et al, 1992), also note 3-to 5-fold higher r 1 affinities than Matsuno et al (1996), reported for the reference compounds (þ)-pentazocine (IC 50 ¼ 13.7 nM) and DTG (IC 50 ¼ 246 nM) in the original SA4503 work. This suggests a systematic, but not easily distinguished, difference between the r 1 receptor assays.…”
Section: Discussionsupporting
confidence: 50%
“…FE93, GK171, FE114, and Ifenprodil were of particular interest, since they exhibited both a high affinity and high selectivity (1,000 to 5,000 times) for PCP 3 binding sites. It is worth noting that the σ 2 (BD1008, Ifenprodil) and the σ 3 (BD737) but not the σ 1 (BD1063) receptor ligands potently interacted with these binding sites (De Costa et al, 1994; Hashimoto and London, 1995; Matsumoto et al, 1995; Monnet et al, 1996). Memantine and CNS1102, two compounds that are currently investigated as potential neuroprotective drugs (Kornhuber et al, 1994; Hu et al, 1997), also displayed a high affinity for PCP 3 binding sites but with a lower selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, BD1008 did not prevent the specific binding of (−)[ 3 H]GK11 to the “non‐NMDA” binding site but slightly inhibited that of [ 3 H]TCP in the forebrain and the molecular layer of the cerebellum. This effect might represent a low‐affinity interaction of [ 3 H]TCP with sigma receptors, since BD1008 was primarily developed as a sigma ligand (De Costa et al, 1994). Indeed, the region‐dependent effect of BD1008 on [ 3 H]TCP specific binding is consistent with the known preferential expression of sigma receptors in the forebrain and the molecular layer of the cerebellum (Largent et al, 1986; Jansen et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…At that time, only a few other compounds were known to display a certain 2 over 1 receptor selectivity. Compounds belonging to the pyrrolidinyl-and carboline-derivatives classes were characterized by a low (at the best around 10-fold) 2 versus 1 receptor selectivity [16,17], far from the excellent selectivity displayed by (+)-morphans. However, opioid and 2 receptors displayed the same enantioselectivity, so that CB64D and CB184 were accompanied also by high opioid affinity displaying just moderate 2 versus opioid receptors selectivity.…”
Section: Classes Of 2 Receptor Ligands Morphansmentioning
confidence: 99%